Practical Aspects of Declarative Languages 15th International Symposium, PADL 2013, Rome, Italy, January 21-22, 2013, Proceedings - Sagonas, Kostis (Programming and Software Engineering, 2013)
This book constitutes the refereed post-proceedings of the 15th International Symposium on Practical Aspects of Declarative Languages, PADL 2013, held in Rome, Italy, in January 2013, co-located with POPL 2013, the 40th Symposium on Principles of Programming Languages. The 17 revised papers presented were carefully reviewed and selected from 33 submissions. The volume features original work emphasizing new ideas and implementation techniques for all forms of declarative concepts, including functional, logic, and constraints.